Indoor air quality assessment in enclosed car park / Nur Shuhada Izam - Izam, Nur Shuhada (Faculty of Architecture, Planning and Surveying, 2015)
Generally, this study concerned about the indoor air quality assessment in enclosed car park. It is related about the building management indoor air control in the commercial building in Plaza Perangsang, Plaza Alam Sentral and Complex PKNS. The aims of the study to assess the indoor air quality in enclosed car park and to determine the concentration of gas in the area. It has three objectives that need to be achieved. Firstly to understanding the important of indoor air quality in enclosed car park, secondly to analyze the effectiveness indoor air quality in enclosed car park, thirdly to measure the reading of indoor air quality enclosed car park and last one is to give recommendation to improve the indoor air quality in enclosed car park. The research methodology that has been implemented during the research is through the sampling of air quality. In this study the sample reading of gas CO and C02 will be collect to assess the level of concentration and it will be collect in unit ppm. The gas reading will be made of 10 minute interval for 1 hour duration in the afternoon and evening. Through the sampling data will be analyses whether the air qualities comply with the requirement and standard of Malaysia guidelines. All the data has been presented or show into the forms of table and graph. Finding shows that the Plaza Alam Sentral has the poor indoor air quality in enclosed car park maybe either the lack maintenance of service, poor ventilation system or design. While the Plaza Perangsang and Complex PKNS in a good condition of air quality. The readings of gas concentration exceed the air quality guidelines. It is supported by the questionnaire session where respondent agree the Plaza Alam Sentral have a poor indoor air quality. Recommendations are made to improve the indoor air quality in enclosed car park to provide the effectiveness of ventilation system.